Multibody mechatronic systems : proceedings of the MUSME Conference held in Huatulco, Mexico, October 21-24, 2014 /: proceedings of the MUSME Conference held in Huatulco, Mexico, October 21-24, 2014. ([2014]) - Unknown
No abstract available